2018
DOI: 10.3892/ol.2018.8314
|View full text |Cite
|
Sign up to set email alerts
|

The anti-tumor effects of Mfn2 in breast cancer are dependent on promoter DNA methylation, the P21Ras motif and PKA phosphorylation site

Abstract: Abstract. Mitofusin 2 (Mfn2) is expressed in numerous human tissues and serves a pivotal role in cell proliferation. However, Mfn2 is considered as an anti-tumor gene, and is silenced in human malignant tumors, including those of breast cancer. However, the mechanisms contributing to Mfn2 silencing and the mechanism of its anti-tumor function in breast cancer remain unclear. In the present study, hypoexpression of Mfn2, and hypermethylation of its promoter, was confirmed in human breast cancer cells and in bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…It may be involved in cervical cancer pathogenesis and might serve as a biomarker of cervical SCC in the future [7]. In our and others studies, Mfn2 could induce Hela cells into mitochondrial apoptosis [8], pancreatic cancer into cell autophagy [9], and breast cancer into DNA methylation [10], as a tumour suppressor in many cancers. Mfn-2 is a mitochondrial outer-membrane protein with GTPase activity involved in mitochondrial fusion and fission and apoptosis regulation [1113].…”
Section: Introductionmentioning
confidence: 91%
“…It may be involved in cervical cancer pathogenesis and might serve as a biomarker of cervical SCC in the future [7]. In our and others studies, Mfn2 could induce Hela cells into mitochondrial apoptosis [8], pancreatic cancer into cell autophagy [9], and breast cancer into DNA methylation [10], as a tumour suppressor in many cancers. Mfn-2 is a mitochondrial outer-membrane protein with GTPase activity involved in mitochondrial fusion and fission and apoptosis regulation [1113].…”
Section: Introductionmentioning
confidence: 91%
“…Recently, it was reported that MFN2 plays an essential role in mitochondrial fusion, which regulates mitochondrial morphology and function in multiple cell types . Meanwhile, MFN2 has been demonstrated to be low expressed in various types of human malignant tumours, such as gastric cancer, hepatocellular cancer, colorectal cancer and breast cancer . Apart from its role in cancer, clinical evidence revealed that dysfunction of MFN2 is also involved in the pathophysiology of several cardiovascular diseases including hypertension, restenosis after angioplasty, cardiac hypertrophy and cardiac oxidative stress injury .…”
Section: Introductionmentioning
confidence: 99%
“…6 Meanwhile, MFN2 has been demonstrated to be low expressed in various types of human malignant tumours, such as gastric cancer, hepatocellular cancer, colorectal cancer and breast cancer. 7,8 Apart from its role in cancer, clinical evidence revealed that dysfunction of MFN2 is also involved in the pathophysiology of several cardiovascular diseases including hypertension, restenosis after angioplasty, cardiac hypertrophy and cardiac oxidative stress injury. 9,10 Intriguingly, MFN2 was found to exert an anti-proliferative effect by inducing more cells at the G0/G1 phase in cultured MCF-7 cells and a rat carotid artery balloon-injury model.…”
Section: Introductionmentioning
confidence: 99%
“…MFN2 promotes cellular apoptosis and inhibits cell proliferation [ 17 , 18 ]. Studies showed that the expression of MFN2 in colorectal cancer tissues and breast cancer tissues is significantly lower than that in normal adjacent tissues [ 19 , 20 ]. These results suggest that MFN2 plays an important role in the occurrence and development of malignant tumors.…”
Section: Introductionmentioning
confidence: 99%